Pengaruh Pembiayaan Bagi Hasil Terhadap Profitabilitas (ROE) Bank Umum Syariah di Indonesia Tahun 2015-2021 - Diah Novianti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to examine the effect of Mudharabah finance and Musyarakah finance to Profitability (ROE) of Islamic Bank in Indonesia from 2015-2021. This study uses multiple linear regression analysis using Eviews 12 to test the research hypothesis. The data used in this study are monthly data of monthly margin profit and ROE from January 2015 to December 2021.The results of this study indicate that partially there is an influence between Mudharabah Finance to Profitability (ROE) of Islamic Bank in Indonesia with t test (2.3378) > t table (1.986) , there is no partial effect between Musyarakah Finance to Profitability (ROE) of Islamic Bank in Indonesia based on with t test (1.508) <t table (1.986. Simultaneously Musharabah Finance and Musyarakah Finance are significant Profitability (ROE) of Islamic Bank in Indonesia , with a value (Ftest 46.873 > Ftable 2.51) and a significance (0.000 <0.05).